Do invasive plants structure microbial communities to accelerate decomposition in intermountain grasslands?. Issue 24 (21st November 2017) - McTee, Michael R.; Lekberg, Ylva; Mummey, Dan; Rummel, Alexii; Ramsey, Philip W.
Abstract: Invasive plants are often associated with greater productivity and soil nutrient availabilities, but whether invasive plants with dissimilar traits change decomposer communities and decomposition rates in consistent ways is little known. We compared decomposition rates and the fungal and bacterial communities associated with the litter of three problematic invaders in intermountain grasslands; cheatgrass ( Bromus tectorum ), spotted knapweed ( Centaurea stoebe ) and leafy spurge ( Euphorbia esula ), as well as the native bluebunch wheatgrass ( Pseudoroegneria spicata ). Shoot and root litter from each plant was placed in cheatgrass, spotted knapweed, and leafy spurge invasions as well as remnant native communities in a fully reciprocal design for 6 months to see whether decomposer communities were species‐specific, and whether litter decomposed fastest when placed in a community composed of its own species (referred to hereafter as home‐field advantage–HFA). Overall, litter from the two invasive forbs, spotted knapweed and leafy spurge, decomposed faster than the native and invasive grasses, regardless of the plant community of incubation. Thus, we found no evidence of HFA. T‐RFLP profiles indicated that both fungal and bacterial communities differed between roots and shoots and among plant species, and that fungal communities also differed among plant community types. Synthesis . These results show that litter from three common invaders to intermountain grasslands decomposes at different rates and cultures microbial communities that are species‐specific, widespread, and persistent through the dramatic shifts in plant communities associated with invasions. Abstract : Litter from common invaders to intermountain grasslands decomposes at different rates and cultures microbial communities that are species‐specific, widespread, and persistent through the dramatic shifts in plant communities associated with invasions. Surprisingly, these decomposer communities that are species‐specific do not accelerate decomposition of litter placed in its own plant community.